Foot drop: an iatrogenic complication of spinal anesthesia - Goyal,Vipin Kumar (2018)
Abstract Background and objectives Foot drop in postoperative period is very rare after spinal anesthesia. Early clinical assessment and diagnostic interventions is of prime importance to establish the etiology and to start appropriate management. Close follow-up is warranted in early postoperative period in cases when patient complain paresthesia or pain during needle insertion or drug injection. Case report A 22-year-old male was undergone lower limb orthopedic surgery in spinal anesthesia. During shifting from postoperative ward footdrop was suspected during routine assessment of regression of spinal level. Immediately the patient was referred to a neurologist and magnetic resonance imaging was done, which was inconclusive. Conservative management was started and nerve conduction study was done on the 4th postoperative day that confirmed pure motor neuropathy of right peroneal nerve. Patient was discharged with ankle splint and physiotherapy after slight improvement in motor power (2/5). Conclusions Foot drop is very rare after spinal anesthesia. Any suspected patient must undergo emergent neurological consultation and magnetic resonance imaging to exclude major finding and need for early surgical intervention.